Reforming Government Public Land Parigi Moutong District Of Sulawesi Province - Maisa, Maisa; Husainy, Haerani (FDI (Forum Dosen Indonesia), 2017)
The main problem discussed in this study is the legal aspect of public land management by the Government. The main legal issues that discussed is the legal basis for the implementation of public land consolidation, land consolidation mechanism and the accuracy of the method of land consolidation by the Local Government Parigi Moutong district, Central Sulawesi. This study uses the type of normative legal research to answer the problem formulation. The results showed that the land consolidation program is one of the legal institutions that used by the government in arranging a settlement area by involving citizens in its implementation through a decree as an instrument of public law while a decree as a private legal instrument containing the agreement of the participants of land consolidation with the government over land Consolidation Team. The program is more appropriate to use the voluntary method as a legal basis for the establishment of legal rules in implementing the land consolidation program in district of Parigi Moutong. It is recommend that the legal basis of land consolidation program remains consistent referring to the applicable law which is adapted with its principle. In addition, Land Consolidation Team should issues land certificates so that all land consolidation participants can ensure the consolidation of rights and the use of land, and the government consistently using voluntary and deliberation method as a settlement of legal dispute in case of disputes.